Ethnic cultural identity education activities for ethnic boarding school students: A case study in the Southern region, Vietnam - Phan, Trong Nam; Nguyen, Thi Thu Hang; Nguyen, Van De; Danh, Trung; Vo, Xuan Hung; Nguyen, Thi Thu Hang (International Journal of Innovative Research and Scientific Studies, 2025)
National cultural identity encompasses the spiritual essence and historical, cultural, and scientific values of a nation. It includes language, writing, folk arts, social customs, beliefs, festivals, and traditional crafts. Educating students about these values fosters understanding of each ethnic group’s soul, shaping personal character, social responsibility, and love for the homeland. Despite this importance, research on cultural identity education in ethnic boarding schools—particularly in Southern Vietnam—remains limited. This region is known for its rich history of ethnic integration and diverse cultural expressions. This study examined the implementation of cultural identity education in 36 ethnic boarding schools in Southern Vietnam. Using a quantitative survey approach, data were collected from 920 participants, including 368 teachers and administrators and 552 students. Results revealed that while educational objectives and content were well established, teaching methods and organizational strategies remained underdeveloped. Specifically, educational organization scored an average of 3.32, indicating systemic weaknesses. These shortcomings hinder the progress of national education reform. The study emphasizes the need for more practical, inclusive approaches that actively promote national cultural identity. The study affirms that Vietnamese cultural values are not static relics, but actively lived and expressed across diverse communities, transcending ethnic and geographical boundaries.